Development of claroline based training design for elementary school teachers in composing learning media - Saputri, Annisa Tiara Widya; Mawardi, Mawardi; Wasitohadi, Wasitohadi (Jurnal Ilmiah Pendidikan Dasar, 2024)
Competence must be possessed by a teacher whose main task is to transfer knowledge to students. There are four competencies that every teacher must have, namely, pedagogic competence, personality competence, social competence, and professional competence. Focusing on the pedagogical competence of teachers has been considered less than optimal. The research conducted used the type of development research (R&D). Claroline-based training design instruments to improve teachers' pedagogic competence in developing learning media in the validity test by media experts obtained a score of 90.7%, which was included in the very high category. In comparison, material experts obtained a score of 79.9%, which was included in the high category, and finally, training design experts obtained a score of 61.3%, which was included in the high category. According to the validity results of the three experts, the Claroline-based training design instrument to improve teachers' pedagogical competence in developing learning media is suitable for use.